Addition of residues and reintroduction of microorganisms in Jatropha curcas cultivated in degraded soil - Santos, Adriana A. [UNESP]; Agustini, Jose A. [UNESP]; Maltoni, Katia L. [UNESP]; Cassiolato, Ana M. R. [UNESP] (Univ Federal Campina Grande, 2016)
The aim of this study was to evaluate, through mycorrhization (root colonization and number of spores of arbuscular mycorrhizal fungi - AMF), leaf acid phosphatase and soil chemical characteristics, the effects of the addition of residues (macrophytes and ash), hydrogel and the reintroduction of microorganisms in a degraded area cultivated with jatropha. Degradation occurred when the surface soil was removed during the construction of a hydroelectric power plant. The experiment was set in a randomized block design, using a 2 x 2 x 4 factorial scheme, i.e., two inoculation treatments (with and without soil-inoculum), two hydrogel treatments (with and without) and four with the addition of residues (macrophytes - MAC, ash, MAC + ash and control, without residues) applied in the planting hole, with 4 replicates and 5 plants in each replicate. Soil from preserved Cerrado area was used as a source of microorganisms, including AMF. The conclusion is that, after 12 months of planting, the hydrogel increased root colonization, while the chemical characteristics of the degraded soil responded positively to the addition of MAC and MAC + ash, with increase in pH and SB and reduction of Al and H + Al. The addition of the soil-inoculum, along with MAC and MAC + ash, promoted higher mycorrhizal colonization and number of spores and reduced amounts of leaf acid phosphatase, indicating increased absorption of P by the host.
Keywords: Jatropha curcas L.; arbuscular mycorrhiza; hydrogel; macrophytes; Cerrado